Pelaksanaan Tugas Dan Wewenang Badan Pengawas Pemilu (Bawaslu) Dalam Mencegah Politik Uang Pada Pemilu 2024 (Studi Kasus Kabupaten Manggarai Barat) - Bahagia, Yovita; Monteiro, Yosef M; Dalima, Maria Susanti (Law Faculty, Nusa Cendana University, 2025)
This study aims to analyze the effectiveness of the Election Supervisory Agency (Bawaslu) of West Manggarai Regency in preventing the practice of money politics in the 2024 Election. The method used is empirical juridical with a socio-legal, conceptual, and legislative approach, involving interviews with stakeholders The results of the study indicate that Bawaslu faces various internal challenges, such as limited human resources (4 district apparatus and 36 sub-district supervisors to supervise 181 regions), minimal APBD budget, and weaknesses in regulations, especially Law No. 7/2017 which does not provide sanctions for recipients of money politics. external challenges include the deep-rooted culture of money politics, low legal awareness in the community - as seen from the acceptance of money or